The Relationship Between Gratitude and Psychological Wellbeing in Adolescents - Sari, Dewi Kumala; Santi, Dyan Evita (International Journal of Social and Management Studies, 2023)
The period of adolescent development is a period of development that is of concern to many people,because this period of development is often referred to as the period of self-discovery. The transition period fromthe period of child development to adulthood often causes serious problems that have an impact on lowpsychological wellbeing. Gratitude possessed by adolescents also affects psychological conditions. Therefore,this study aims to examine the relationship between gratitude and psychological wellbeing in adolescents. Toachieve this goal, this research uses a quantitative approach. The sample in this study were class IX students ofSMPN 1 Prambon Sidoarjo. The instrument used is the instrument of psychological wellbeing and theinstrument of the gratitude questionnaires six item form (GQ-6). The data analysis technique used in thisresearch is correlation coefficient analysis to test the degree of relationship between variables. The results ofthis study obtained that the correlation coefficient between the gratitude variable and the psychologicalwellbeing (PWB) variable was 0.601, which means that the correlation between gratitude and psychologicalwellbeing (PWB) is very strong. The hypothesis of this study is accepted that there is a relationship betweengratitude and psychological wellbeing (PWB) in adolescents.